Regional study of the Archean to Proterozoic crust at the Sudbury Neutrino Observatory (SNO+), Ontario: Predicting the geoneutrino flux. (23rd October 2014) - Huang, Yu; Strati, Virginia; Mantovani, Fabio; Shirey, Steven B.; McDonough, William F.
Abstract The SNO+ detector that is currently under construction in Ontario, Canada, will be a new kiloton‐scale liquid scintillation detector with the capability of recording geoneutrino events that can be used to constrain the strength of the Earth's radiogenic power, and in turn, to test compositional models of the bulk silicate Earth (BSE). We constructed a detailed 3‐D model of the regional crust centered at SNO+ from compiled geological, geophysical, and geochemical information. Crustal cross sections obtained from refraction and reflection seismic surveys were used to characterize the crust and assign uncertainties to its structure. The average Moho depth in the study area is 42.3 ± 2.6 km. The upper crust was divided into seven dominant lithologic units on the basis of regional geology. The abundances of U and Th and their uncertainties in each upper crustal lithologic unit were determined from analyses of representative outcrop samples. The average chemical compositions of the middle and lower crust beneath the SNO+ region were determined by coupling local seismic velocity profiles with a global compilation of the chemical compositions of amphibolite and granulite facies rocks. Monte Carlo simulations were used to predict the geoneutrino signal originating from the regional crust at SNO+ and to track asymmetrical uncertainties of U and Th abundances. The total regional crust contribution of the geoneutrino signal at SNO+ is predicted to be <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m45jjp3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />15.6−3.4+5.3</alternatives> TNU (a Terrestrial Neutrino Unit is one geoneutrino event per 1032 target protons per year), with the Huronian Supergroup near SNO+ dominantly contributing <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m45jjnj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />7.3−3.0+5.0</alternatives> TNU to this total. Future systematically sampling of this regional unit and denser seismic surveys will better model its composition and structure, and thus reduce the uncertainty on geoneutrino signal at SNO+. The bulk crustal geoneutrino signal at SNO+ is estimated to be <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m45jjm0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />30.7−4.2+6.0</alternatives> TNU, which is lower than that predicted in a global‐scale reference model that uses an average composition of the global upper continental crust, due to the fact that Archean to Proterozoic Canadian Shield has lower U and Th concentrations. Finally, without accounting for uncertainties on the signal from continental lithospheric mantle and convecting mantle, the total geoneutrino signal at SNO+ is predicted to be <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m45jjkf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />40−4+6</alternatives> TNU.